Pediatric Dorsal Intradural Extra-Medullary Epidermoid Cyst (Non-Dysraphic): An Illustrative Case with Literature Review (Journal of National Institute of Neurosciences Bangladesh, 2023)
A spinal epidermoid cyst is a rare congenital tumour that may be associated with spinal dysraphism. Congenital spinal epidermoid cysts without spinal dysraphism are rare. Here we are reporting a rare and interesting case of thoracic Intradural extra-medullary epidermoid cyst not associated with spinal dysraphism. Epidermoid cysts (EC) represent less than 1.0% and are rarely seen as an intradural extra-medullary spinal cord tumor.  Preoperative Clinico- Radiological assumption is important for surgical planning.Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):88-95